Strategi Penggunaan Content Marketing Pada Pengguna TikTok dan Instagram Berdasarkan Audience Behaviour di Perusahaan X - -, Khairunnisa; Asyari, Hasyim (UI Scholars Hub, 2024)
This study aims to examine the differences in TikTok and Instagram user behavior, useful for marketing strategy planning, consumer behavior research, and content creation suitable for TikTok and Instagram platforms in the Company X account. The results of this study are expected to make a positive contribution to the understanding of the role of social media and how differences in user behavior can shape further transformation in the evolving digital ecosystem. This research uses a quantitative descriptive method that compares two advertising contents uploaded on Tik Tok social media and Instagram social media. The objects contained in this study include TikTok, Instagram, and users of both social media platforms. From this research it can be concluded that content creation for TikTok and Instagram requires several different treatments due to differences in user behavior, both for the promotion, education, entertainment, and event categories.